Ultraviolet curing adhesive and preparation method thereof
Through the use of the fatty polyurethane acrylic and other components of the fatty family in ultraviolet light curing, it solves the phenomenon of oxygen blocking, realizes low water vapor transmission rate and high insulation, and improves dry performance and stability.
Patent Information
- Application Number
- CN202411694813.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-24
AI Technical Summary
During the curing process, the ultraviolet curing glue consumes free radicals, causing partial failure to cure completely, resulting in oxygen resistance to polymerization, which affects the normal use and life of the product.
Use the fatty polyurethane acrylate as the main component, with active diluing agents, light causes, spouse agents, coupling agents and tactile agents with a specific proportion. The drying performance and stability of the glue.
The low water vapor transmission rate and high insulation of ultraviolet light curing glue are achieved, the drying performance is improved, the yellow change after solidification is avoided, the depth of solidification is maintained, and the stability and application performance of the product are improved.
Smart Images

Figure BDA0005151848150000021 
Figure BDA0005151848150000041 
Figure BDA0005151848150000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of curing adhesive preparation, and in particular to an ultraviolet curing adhesive and a preparation method thereof. Background Art
[0002] UV curing, or ultraviolet light curing, is a new environmentally friendly, low-VOC emission technology that emerged in the 1960s. It has been rapidly developed in my country since the 1980s. It is fast and efficient, and can be cured in a few seconds under ultraviolet light. It can achieve different functions after curing with acrylic resins of different systems.
[0003] As UV curing technology gradually matures, the performance of UV curing adhesives is becoming more and more perfect, and the functions that can be realized are becoming more and more diverse. Therefore, it has also been applied to many fields. In recent years, its application in the automotive and consumer electronics fields has gradually increased. Taking the consumer electronics field as an example, UV curing adhesives can be used for display module caulking, component waterproof sealing, wire harness bonding protection, screen frame protection, etc., and can also be used as light-shielding adhesives by adding a small amount of color paste or color powder without affecting curing.
[0004] However, during the curing process of UV-curing adhesive, oxygen will consume some free radicals, resulting in the inability to completely cure the part in contact with oxygen, which is called oxygen inhibition. The existence of oxygen inhibition may cause UV-curing adhesive to pollute the product in actual application, affecting the normal use and life of the product. Common methods to inhibit oxygen inhibition include: isolating oxygen, increasing the amount of photoinitiator added, increasing the curing energy, adding tertiary amines and thiols, etc.
[0005] In addition, when UV-curing adhesive is used as waterproof sealant, it needs to have low water absorption and water vapor transmission rate after curing. Polybutadiene polyurethane acrylate has good hydrophobicity due to its low polarity and long aliphatic carbon chain. It can keep the water absorption and water vapor transmission rate at a low level after curing by combining with some low-polarity active diluents or adding some fluorine-containing additives, while having good insulation and bending resistance. However, oxygen inhibition of polybutadiene polyurethane acrylate is relatively obvious during the curing process, which is a problem that needs to be solved urgently.
[0006] In the prior art, Chinese patent CN111138966A discloses a flexible UV light-curing coating and its preparation method and application, which uses polybutadiene polyurethane acrylate as the main resin and is used together with silicone-modified acrylate. It has the advantages of good low-temperature bending resistance, low water vapor permeability, fast curing, good elasticity, high gloss, etc. of polybutadiene polyurethane acrylate. At the same time, the presence of silicon-oxygen bonds increases the flexibility, water resistance and heat resistance of the coating. However, silicone oil may seep out during subsequent use, thereby causing pollution to the product.
[0007] Chinese patent CN115521754A discloses an acrylic adhesive with low water absorption and a preparation method thereof, which uses polybutadiene polyurethane acrylate as the main resin, has low water absorption, and still has good insulation performance under high temperature and high humidity conditions, but has poor surface dryness after curing. Summary of the invention
[0008] The purpose of the present invention is to provide a UV curing adhesive to overcome the above technical problems.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] The invention provides an ultraviolet light curing adhesive, which comprises, by weight: 30-40 parts of aliphatic polyurethane acrylate; 50-60 parts of active diluent; 3-5 parts of photoinitiator; 0.3-1 parts of co-initiator; 1-2 parts of coupling agent; 3-5 parts of thixotropic agent; the co-initiator comprises piperonyl alcohol and its derivatives.
[0011] Optionally, the aliphatic polyurethane acrylate comprises an acryloxy group and a urethane bond, and has the general formula:
[0012]
[0013] Where n is a natural number between 27 and 65;
[0014] R1 is selected from acryloyloxyethyl, methacryloyloxyethyl or acryloyloxypropyl;
[0015] R2 is selected from cyclohexyl or straight chain alkyl.
[0016] Optionally, the viscosity of the aliphatic polyurethane acrylate at 60° C. is 1000-60000 centipoise.
[0017] Optionally, the aliphatic polyurethane acrylate is polybutadiene polyurethane acrylate.
[0018] Optionally, the active diluent includes one or more of isobornyl acrylate, isobornyl methacrylate, isodecyl acrylate, 2-phenoxyethyl acrylate, dodecyl acrylate, trimethylolpropane formal acrylate, alkoxylated tetrahydrofuran acrylate, alkoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A dimethacrylate, 1,6-hexanediol dimethacrylate, 1,3-butanediol dimethacrylate, pentaerythritol triacrylate or tricyclodecane dimethanol diacrylate.
[0019] Optionally, the photoinitiator includes a cleavage-type photoinitiator or a hydrogen abstraction-type photoinitiator; the cleavage-type photoinitiator includes: 1-hydroxy-cyclohexyl-phenyl ketone, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinephenyl)-1-butanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2,4,6-trimethylbenzoyl-diphenyl One or more of phosphine oxide, 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide, 2-benzoylmethyl-1-[4-(morpholinyl)phenyl]-1,2-propanedione, 2,2-dimethoxy-2-phenylacetophenone or 2-hydroxy-2-methyl-1-phenyl-1-propanone; the hydrogen abstraction type photoinitiator includes one or more of benzophenone, 4-phenylbenzophenone, 4-phenylthiobenzophenone or 2-isopropylthioxanthone.
[0020] Optionally, the coupling agent includes one or more of vinyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane or p-phenyltrimethoxysilane.
[0021] Optionally, the thixotropic agent includes hydrophobic fumed silica.
[0022] The present invention also provides a method for preparing a UV-curing adhesive, comprising: mixing and stirring aliphatic polyurethane acrylate, a reactive diluent, and a coupling agent to obtain a first mixture; adding a photoinitiator and a co-initiator to the first mixture and stirring to obtain a second mixture; adding a thixotropic agent to the second mixture and stirring to obtain the UV-curing adhesive.
[0023] Optionally, the stirring speed of the first mixture is 1200-1500 r / min, and the stirring time is 3-5 minutes; the stirring speed of the second mixture is 1500-2000 r / min, and the stirring time is 5-10 minutes; the stirring speed of the final mixture is 600-800 r / min, and the stirring time is 2-3 minutes.
[0024] The UV curing adhesive of the present invention uses aliphatic polyurethane acrylate as a main component, which has low polarity and long carbon chain. With other components in a specific ratio, the curing adhesive has good hydrophobicity, thereby achieving low water vapor permeability, and also has good insulation and bending resistance. In addition, using piperonyl alcohol and its derivatives as co-initiators can give full play to their hydrogen donor function and effectively improve the surface drying performance of the curing adhesive.
[0025] By rationally designing the ratio of each component and the preparation process, the UV curing adhesive of the present invention not only has good processing performance, but also exhibits excellent surface drying performance during the curing process, and does not significantly yellow after curing. At the same time, by adopting a specific stirring process, the components can be fully mixed and evenly mixed, further improving the stability of product performance. DETAILED DESCRIPTION
[0026] The present invention will be described in more detail below, wherein preferred embodiments of the present invention are shown, and it should be understood that those skilled in the art can modify the present invention described herein, and still achieve the beneficial effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art, and not as a limitation of the present invention.
[0027] The present invention is described in more detail by way of example in the following paragraphs. Advantages and features of the present invention will become more apparent from the following description.
[0028] The invention provides an ultraviolet light curing adhesive, which comprises, by weight: 30-40 parts of aliphatic polyurethane acrylate; 50-60 parts of active diluent; 3-5 parts of photoinitiator; 0.3-1 parts of co-initiator; 1-2 parts of coupling agent; 3-5 parts of thixotropic agent; the co-initiator comprises piperonyl alcohol and its derivatives.
[0029] Specifically, the aliphatic polyurethane acrylate comprises an acryloxy group and a urethane bond, and its general formula is:
[0030]
[0031] Where n is a natural number between 27 and 65.
[0032] The structural formula of R1 is any of the following:
[0033]
[0034] The structural formula of R2 is:
[0035] Specifically, the viscosity of the aliphatic polyurethane acrylate at 60° C. is 1000-60000 centipoise (cps).
[0036] Preferably, the aliphatic polyurethane acrylate is polybutadiene polyurethane acrylate.
[0037] In a specific example, the aliphatic polyurethane acrylate can be selected from one or more of CN8004NS, CN8003NS, CN8010NS, CN8883NS, CN8888NS, CN9004, CN9014NS, CN9014HV, CN9178NS or CN9001NS from Sartomer.
[0038] Specifically, the active diluent includes one or more of isobornyl acrylate, isobornyl methacrylate, isodecyl acrylate, 2-phenoxyethyl acrylate, dodecyl acrylate, trimethylolpropane formal acrylate, alkoxylated tetrahydrofuran acrylate, alkoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A dimethacrylate, 1,6-hexanediol dimethacrylate, 1,3-butanediol dimethacrylate, pentaerythritol triacrylate or tricyclodecane dimethanol diacrylate.
[0039] Specifically, the photoinitiator includes a cleavage-type photoinitiator or a hydrogen abstraction-type photoinitiator.
[0040] The cleavage-type photoinitiator includes one or more of 1-hydroxy-cyclohexyl-phenyl ketone (184), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (819), 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone (379), 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone (907), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide (MBP), 2-benzoylmethyl-1-[4-(morpholino)phenyl]-1,2-propanedione (369), 2,2-dimethoxy-2-phenylacetophenone (651) or 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173).
[0041] The hydrogen abstraction type photoinitiator includes one or more of benzophenone (BP), 4-phenylbenzophenone (PBZ), 4-phenylthiobenzophenone (BMS) or 2-isopropylthioxanthone (ITX).
[0042] Specifically, the coupling agent includes one or more of vinyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane or p-phenyltrimethoxysilane.
[0043] Specifically, the thixotropic agent includes hydrophobic fumed silica.
[0044] In a specific example, the hydrophobic fumed silica can be selected from one or more of Cabot TS-720, Yingxing SD2006N, Yingxing SD2006ME, Yingxing SD3006ME, Evonik R974, Evonik R711, Evonik R805 or Wacker H20.
[0045] According to the composition of the above-mentioned UV-curable adhesive, the performance of the UV-curable adhesive provided by the present invention was tested through three groups of examples and three groups of comparative examples.
[0046] Example 1
[0047] Weigh the following raw materials by weight:
[0048] Table 1
[0049] raw material Dosage Polybutadiene polyurethane acrylate 30g Isobornyl acrylate IBOA 35g N,N-DimethylacrylamideDEAA 5g Silane coupling agent KH560 1g Piperonyl acetate 0.24g Photoinitiator 184 3g Photoinitiator 819 1g Hydrophobic fumed silica TS-720 3g
[0050] The specific preparation steps are as follows:
[0051] (1) adding polybutadiene polyurethane acrylate, isobornyl acrylate, N,N-dimethylacrylamide and silane coupling agent KH560 into a stirring container, stirring at a speed of 1200 r / min for 4 minutes to obtain a first mixture;
[0052] (2) adding piperonyl acetate, photoinitiator 184 and photoinitiator 819 to the first mixture, stirring at a speed of 1500 r / min for 8 minutes to obtain a second mixture;
[0053] (3) Add hydrophobic fumed silica TS-720 to the second mixture, and stir at a speed of 600 r / min for 2.5 minutes to obtain a UV-curable adhesive.
[0054] Example 2
[0055] A preparation of a UV curing adhesive, weigh the following raw materials by weight:
[0056] Table 2
[0057] raw material Dosage Polybutadiene polyurethane acrylate 30g Isobornyl acrylate IBOA 35g N,N-DimethylacrylamideDEAA 5g Silane coupling agent KH560 1g Piperonyl acetate 0.4g Photoinitiator 184 3g Photoinitiator 819 1g Hydrophobic fumed silica TS-720 3g
[0058] The preparation steps are the same as in Example 1.
[0059] Example 3
[0060] A preparation of a UV curing adhesive, weigh the following raw materials by weight:
[0061] Table 3
[0062]
[0063]
[0064] The preparation steps are the same as in Example 1.
[0065] Comparative Example 1
[0066] A low water permeability UV curing adhesive is prepared, the formula is the same as that of Example 2, but without adding piperonyl acetate.
[0067] Comparative Example 2
[0068] A preparation method of a high surface dry UV curing adhesive is as follows:
[0069] Table 4
[0070] raw material Dosage Runao FSP5508 30g Isobornyl acrylate IBOA 15g Tetrahydrofuranyl acrylate THFA 5g Silane coupling agent KH560 1g Photoinitiator 184 2.5g Photoinitiator 819 0.5g Hydrophobic fumed silica TS-720 2g
[0071] The preparation steps are the same as in Example 1.
[0072] Comparative Example 3
[0073] A preparation of a UV curing adhesive containing EDB, the formula is the same as that of Example 2, but the piperonyl acetate is replaced by an amine co-initiator EDB.
[0074] Performance Testing:
[0075] The following performance tests were performed on Examples 1-3 and Comparative Examples 1-3 respectively.
[0076] (1) Surface dry test:
[0077] Take a small amount of the above composition and place it on a 100*25*6mm glass substrate. Use a film scraper to scrape out a 200um thick film. Use a UV LED light source with a wavelength of 365nm and 1000mw / cm 2 After irradiation for 5 seconds, sprinkle spherical quartz powder SHA0065 on the surface of the cured film, and gently wipe off the excess spherical quartz powder on the surface with a non-woven cloth. Observe the residual amount of spherical quartz powder on different films. The better the surface dryness after curing, the less spherical quartz powder remains on the film.
[0078] (2) Water vapor transmission rate test:
[0079] Tested in accordance with GB / T 1037-2021, the test sample is 300um thick, 100mm long and 100mm wide, with uniform thickness and no bubbles; the curing conditions are 365nm UV LED light source, 1000mw / cm 2 Irradiate for 5S; test conditions are 55℃ / 95RH.
[0080] (3) Curing depth test:
[0081] The compositions prepared in the above examples were injected into a curing depth test mold and illuminated with a UVLED light source with a wavelength of 365 nm and a power of 500 mw / cm 2 After irradiation for 10 seconds, the cured sample was demoulded and taken out, the incompletely cured part at the bottom was removed, and the effective curing depth was measured with a vernier caliper.
[0082] The test results are shown in Table 5 below:
[0083] Table 5: Test results summary
[0084]
[0085] The main resin used in Examples 1-3 and Comparative Examples 1 and 3 is polybutadiene polyurethane acrylate, and the main resin used in Comparative Example 2 is polycarbonate polyurethane acrylate.
[0086] From the above test results, we can see that:
[0087] When Examples 1-3 and Comparative Examples 1 and 3 are compared with Comparative Example 2, it can be seen that the UV-curable adhesive with polybutadiene polyurethane acrylate as the main resin has low polarity and a much lower water vapor permeability than the common UV-curable adhesive with polycarbonate polyurethane acrylate as the main resin, which is more advantageous in some applications requiring water vapor barrier.
[0088] Comparing Examples 1-3 and Comparative Example 3 with Comparative Example 1, it can be seen that after adding the amine co-initiator EDB and the amine-free piperonyl alcohol derivative - piperonyl acetate, the spherical quartz powder residue on the surface of the cured film is reduced and the surface dryness is improved.
[0089] Comparison between Example 2 and Comparative Example 3 shows that, under the same addition amount, Example 2, which added the piperonyl acetate derivative, did not turn yellow after curing, while Comparative Example 3, which added the amine co-initiator EDB, turned yellow significantly after curing. Since yellowing during curing will affect the penetration of ultraviolet light and reduce the curing depth, it can be seen from the test results that the curing depth of Example 2 is much greater than that of Comparative Example 3. However, as the addition amount of piperonyl acetate in Examples 1-3 gradually increased, the curing depth decreased from the highest 6.1 mm to 5.1 mm, which was 0.4 mm lower than that of Comparative Example 1 without piperonyl acetate.
[0090] In polybutadiene polyurethane acrylate UV-curing adhesives with low water vapor permeability, amine co-initiators and piperine alcohol and its derivatives can be used as hydrogen donor co-initiators to enhance sensitivity and improve surface drying. However, since amine co-initiators will turn yellow during curing, the curing depth is far less than that of piperine alcohol and its derivatives co-initiators that do not contain amines. Excessive use will reduce the curing effect, so it is necessary to control the amount of piperine alcohol and its derivatives co-initiators.
[0091] In summary, the UV curing adhesive system provided by the present invention uses aliphatic polyurethane acrylate represented by polybutadiene polyurethane acrylate as the main component, so that the cured adhesive has a lower water vapor permeability; piperonyl alcohol and its derivatives are used as co-initiators to improve the surface drying performance while not causing yellowing after curing, thereby maintaining a large curing depth.
[0092] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A UV curing adhesive, characterized in that: By weight, it contains: Aliphatic polyurethane acrylate 30-40 parts; 50-60 parts of active diluent; 3-5 parts of photoinitiator; 0.3-1 part of co-initiator; 1-2 parts of coupling agent; Thixotropic agent 3-5 parts; The auxiliary initiator includes piperonyl alcohol and its derivatives.
2. The UV curing adhesive according to claim 1, characterized in that: The aliphatic polyurethane acrylate comprises an acryloxy group and a urethane bond, and its general formula is: Where n is a natural number between 27 and 65; R1 is selected from acryloyloxyethyl, methacryloyloxyethyl or acryloyloxypropyl; R2 is selected from cyclohexyl or straight chain alkyl.
3. The UV curing adhesive according to claim 1, characterized in that: The viscosity of the aliphatic polyurethane acrylate at 60° C. is 1,000-60,000 centipoise.
4. The UV curing adhesive according to claim 1, characterized in that: The aliphatic polyurethane acrylate is polybutadiene-based polyurethane acrylate.
5. The UV curing adhesive according to claim 1, characterized in that: The active diluent includes one or more of isobornyl acrylate, isobornyl methacrylate, isodecyl acrylate, 2-phenoxyethyl acrylate, dodecyl acrylate, trimethylolpropane formal acrylate, alkoxylated tetrahydrofuran acrylate, alkoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A dimethacrylate, 1,6-hexanediol dimethacrylate, 1,3-butanediol dimethacrylate, pentaerythritol triacrylate or tricyclodecane dimethanol diacrylate.
6. The UV curing adhesive according to claim 1, characterized in that: The photoinitiator includes a cleavage-type photoinitiator or a hydrogen-abstraction-type photoinitiator; The cleavage-type photoinitiator includes one or more of 1-hydroxy-cyclohexyl-phenyl ketone, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide, 2-benzoylmethyl-1-[4-(morpholino)phenyl]-1,2-propanedione, 2,2-dimethoxy-2-phenylacetophenone or 2-hydroxy-2-methyl-1-phenyl-1-propanone; The hydrogen abstraction type photoinitiator includes one or more of benzophenone, 4-phenylbenzophenone, 4-phenylthiobenzophenone or 2-isopropylthioxanthone.
7. The UV curing adhesive according to claim 1, characterized in that: The coupling agent includes one or more of vinyl trimethoxy silane, γ-glycidyloxypropyl trimethoxy silane, γ-aminopropyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane, 3-mercaptopropyl methyl dimethoxy silane, 3-mercaptopropyl trimethoxy silane or p-phenylene trimethoxy silane.
8. The UV curing adhesive according to claim 1, characterized in that: The thixotropic agent includes hydrophobic fumed silica.
9. A method for preparing a UV-curable adhesive, characterized in that: Mixing and stirring aliphatic polyurethane acrylate, reactive diluent, and coupling agent to obtain a first mixture; Adding a photoinitiator and a co-initiator into the first mixture and stirring to obtain a second mixture; A thixotropic agent is added into the second mixture and stirred to obtain the UV curing adhesive.
10. The method for preparing the UV curing adhesive according to claim 9, characterized in that: The stirring speed of the first mixture is 1200-1500 r / min, and the stirring time is 3-5 minutes; The stirring speed of the second mixture is 1500-2000r / min, and the stirring time is 5-10 minutes; The final mixture is stirred at a speed of 600-800 r / min and for 2-3 minutes.
Citation Information
Patent Citations
Flexible UV photocureable coating, and preparation method and application thereof
CN111138966A
Acrylic acid adhesive with low water absorption rate and preparation method thereof
CN115521754A
Cited By
UV sealant for fastener gasket and preparation method of UV sealant
CN121319859A